The effect of electric transmission constraints on how power generation companies bid in the colombian electrical power market (2010)
This paper presents the results of research about the effect of transmission constraints on both expected electrical energy to be dispatched and power generation companies’ bidding strategies in the Colombian electrical power market. The proposed model simulates the national transmission grid and economic dispatch by means of optimal power flows. The proposed methodology allows structural problems in the power market to be analyzed due to the exclusive effect of trans- mission constraints and the mixed effect of bidding strategies and transmission networks. A new set of variables is proposed for quantifying the impact of each generation company on system operating costs and the change in expected dispatched energy. A correlation analysis of these new variables is presented, revealing some interesting linearities in some generation companies’ bidding patterns.